2019
DOI: 10.1080/21691401.2019.1645149
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy and safety of statin treatment after carotid artery stenting

Abstract: Objective: The randomized controlled trail was carried out to investigate the influence of statin pretreatment on clinical efficacy of carotid artery stenting (CAS). Methods: 160 eligible patients were randomly divided into statin group (n ¼ 82) and control group (n ¼ 78). The patients in statin group received 40 mg atorvastatin daily 7 days before operation. Major endpoints included transient ischemic attack (TIA), stroke, death, myocardial infarction (MI), and other cardiac adverse events within 30 days afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Since then, one randomized control trial (RCT) and three retrospective studies have been published with controversial results. In particular, the RCT confirmed that patients receiving statins had a lower incidence of post-operative TIAs and stroke in comparison to placebo receivers [91]. However, the latest three retrospective studies did not detect any benefit from statin administration in terms of stroke incidence [92][93][94].…”
Section: Perioperative Treatment With Statins Of Patients With Caroti...mentioning
confidence: 84%
“…Since then, one randomized control trial (RCT) and three retrospective studies have been published with controversial results. In particular, the RCT confirmed that patients receiving statins had a lower incidence of post-operative TIAs and stroke in comparison to placebo receivers [91]. However, the latest three retrospective studies did not detect any benefit from statin administration in terms of stroke incidence [92][93][94].…”
Section: Perioperative Treatment With Statins Of Patients With Caroti...mentioning
confidence: 84%
“…They may also reduce the reabsorption of contrast agents in renal tubules [ 1 , 10 , 12 , 13 , 28 37 ]. Previous studies had shown that loading doses with statins in pre-treated patients before PCI could reduce the myocardial damage and intra-hospital cardiac events, possibly via antioxidant and anti-inflammatory effects, as well as endothelin secretion [ 29 , 37 , 38 ]. Early observational trials and meta-analyses on statin failed to show its beneficial effects on CIN prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Seventeen publications with 26 arms including 3010 participants who received statins and 2968 participants in control groups who did not receive statins or received placebo were included in this meta-analysis. Among them, 12 publications were performed in Asian countries [47][48][49][50][51][52][53][54][55][56][57], 4 publications in European countries [58][59][60][61], and only one study in the USA [62]. Overall population analysis showed that statins decreased the serum level of hs-CRP (WMD = −0:97 mg/L; 95% CI: -1.26 to -0.68 mg/L; P < 0:001; I 2 : 98.2, P heterogeneity > 0:001, Figure 2).…”
Section: Meta-analyses Of the Effect Of Statins On The Serum Level Of Hs-crpmentioning
confidence: 99%